In the Eyes of Those Who Were Randomized: Perceptions of Disadvantaged Older Adults in a Tai Chi Trial. (13th December 2018) - Lo, On-Yee; Conboy, Lisa A; Rukhadze, Alexandra; Georgetti, Caroline; Gagnon, Margaret M; Manor, Brad; Lachman, Margie E; Lipsitz, Lewis A; Wayne, Peter M
Abstract: Background and Objectives: Older adults living in subsidized housing have typically been excluded from exercise intervention studies. We conducted a qualitative study to explore the perceived physical, psychological, social, and economic factors that influenced participation in and adherence to a year-long Tai Chi intervention within an ongoing cluster-randomized controlled trial (RCT) for older adults living within subsidized housing facilities. Research Design and Methods: Focus groups were held with participants of the RCT who were allocated to the trial's Tai Chi intervention. Individual phone interviews were conducted with those allocated to Tai Chi who had low adherence or who had withdrawn their participation from the study. Emergent themes were extracted using grounded-theory methods. Results: In this qualitative study, we enrolled 41 participants who were allocated to the RCT's Tai Chi intervention: 38 completed and 3 withdrew from the study. Average Tai Chi class attendance was 64.3%. Pragmatic factors that led to higher adherence and retention included: locating classes within each facility; providing programs at no cost; and deployment of a skilled research support team. In addition, the use of an accessible, simplified Tai Chi program improved confidence, social support, self-efficacy, and self-reported improvements in physical and psychological well-being. Discussion and Implications: Perceived physical, psychological, social benefits, and self-efficacy likely enhance adherence and retention to research-based Tai Chi interventions for older adults. Delivering an on-site, no cost, and supportive program appears critical to overcoming financial and environmental barriers to participation for those living within subsidized housing.